Openness in public procurement markets: Time for a reality check - Patrick A. Messerlin (European Centre for International Political Economy (ECIPE), 2013)
The European Parliament hearings on the Commission's proposal for a "Regulation establishing rules on the access of third countries' goods and services to the EU internal market in public procurement" offers an opportunity to review two key pillars of the proposal. First, the Directive proponents claim that the EU public procurement markets are much more open than those of its main partners. Second, they assume that the threat of the "reciprocity" clause (allowing the EU to deny access to EU public procurement markets to firms originating from countries with public procurement markets that the EU would feel less open than its own markets) is credible. The paper provides robust evidence that the EU public procurement markets are definitely not more open than those of its main partners. It first shows that, when one compares what is comparable, the impact assessment working document on which the Directive proposal relies fails to support the EU claim. Moreover, the paper provides a robust and exhaustive evidence (based on National Accounts) of the fact that the EU public procurement markets are often less open than those of its main partners. (...)
Keywords: 330; Öffentlicher Auftrag; EU-Vergaberecht; EU-Binnenmarkt; EU-Staaten